2015
DOI: 10.1007/s13277-015-3281-x
|View full text |Cite
|
Sign up to set email alerts
|

The platelet-to-lymphocyte ratio predicts poor survival in patients with huge hepatocellular carcinoma that received transarterial chemoembolization

Abstract: Inflammation is particularly strong in huge hepatocellular carcinoma (HCC). However, it is unclear whether the platelet-to-lymphocyte ratio (PLR), as an inflammatory-related marker, can predict survival of patients with huge HCC. In this study, we enrolled 291 patients with huge HCC (diameter over 10 cm) who were undergoing repeated transarterial chemoembolization (TACE) at our institute. The baseline PLR was calculated from complete serum blood counts before the first chemoembolization. We found that a baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 35 publications
(32 reference statements)
0
35
0
1
Order By: Relevance
“…All these indices can be easily calculated based on routinely performed blood tests in the clinical work-up. For PLR, it can be used to predict the prognosis of HCC patients receiving transarterial chemoembolization [24], thermal ablation [25], or partial hepatectomy [26]. Our previous work also confirmed that pre-transplant elevated PLR was associated with a high proportion of multiple tumors, large tumor size, micro- and macrovascular invasion, and predicted post-transplant tumor recurrence [12].…”
Section: Discussionmentioning
confidence: 77%
“…All these indices can be easily calculated based on routinely performed blood tests in the clinical work-up. For PLR, it can be used to predict the prognosis of HCC patients receiving transarterial chemoembolization [24], thermal ablation [25], or partial hepatectomy [26]. Our previous work also confirmed that pre-transplant elevated PLR was associated with a high proportion of multiple tumors, large tumor size, micro- and macrovascular invasion, and predicted post-transplant tumor recurrence [12].…”
Section: Discussionmentioning
confidence: 77%
“…Nine studies did not meet the inclusion criteria and were therefore excluded. Ultimately, 11 eligible studies, comprising a total of 2,507 patients, were considered eligible for the meta-analysis [1626]. The PRISMA flow diagram of the study selection process was shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…In colorectal cancer and cervical cancer, a higher PLR was associated with a higher rate of lymph node metastasis [10, 42]. Xue TC et al observed that a high PLR predicts poor survival in patients with advanced hepatocellular carcinoma who received TACE [23]. To the best of our knowledge, this is the first meta-analysis to integrate recent studies of the relationship between these two inflammatory markers (the NLR and PLR) and the survival of HCC patients receiving diverse treatments.…”
Section: Discussionmentioning
confidence: 99%